IMPLEMENTASI MODUL CITRA DALAM PRAKTIK KEPERAWATAN ANAK UNTUK MENURUNKAN KECEMASAN ANAK PRASEKOLAH YANG MENJALANI RAWAT INAP DI RUMAH SAKIT - Citra Suraya; Aris Citra Wisuda; Tukimin bin Sansuwito; Masniati Arafah; Fermata Sari; Dian Emiliasari; Isrizal; Nuriza Agustina; Rifka Zalila (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2025)
Anxiety in preschool children during hospitalization can affect their psychological well-being, cooperation during procedures, and recovery process. This community service program aimed to implement the CITRA Module (Communication Through Interactive Therapeutic and Reflective Storytelling Approach) in nursing practice to reduce anxiety among hospitalized preschool children at Siti Khadijah Islamic Hospital Palembang. The program was conducted from July to September 2025 and involved 10 nurses as training participants and 30 preschool children as intervention recipients. The method applied was training and education combined with clinical mentoring, including therapeutic storytelling education, simulation of CITRA implementation, direct clinical practice in pediatric wards, and evaluation through descriptive observation of children’s behavior and emotional responses. The results of descriptive evaluation showed a notable improvement in nurses’ therapeutic communication skills after training and mentoring. In addition, approximately 80% of children demonstrated a decrease in anxiety indicators such as excessive crying, physical tension, and fear of procedures. The CITRA Module proved to be feasible and practical to implement, enabling nurses to build more positive therapeutic interactions with children and enhance the quality of pediatric nursing care. This program is recommended for sustainable implementation in pediatric clinical nursing practice.